"Análisis de las variaciones de los elementos nutricinales en el cultivo de palma aceitera (Elais guineensis Jacq) durante la época seca en la zona de Quevedo-Los Ríos". - Barzola Suárez, Byron Ronald (2012)
The present investigation was developed in the country property Pepita of property of the company " AGROAEREO " located in the km 7 via Quevedo - Rcto. The China county of The Rivers. He/she thought about as objective; to determine the variations of the nutritional contents by means of analysis to foliate in the cultivation of palm oil bottle. They took samples foliares in three areas where the age of the cultivation reaches the four years and it is in production process, leaving from the month of June with intervals of two months until the month of December; elect the leaf numbers 17 of the plants, chord to studies carried out by investigators. Of the alone samples the central part of the foliolos was extracted to send them to the laboratory for its respective analysis. Were the data subjected to the test of t " student " (p? 0.05) for the comparison, statisticians were used like: he/she mediates, standard deviation, variation coefficient, to determine differences among stockings and to check the proposed hypothesis. A registration so much was taken weekly as monthly of the production of the evaluated sectors. He/she was proven that the elements like nitrogen, match, zinc and manganese generally maintained an increase from June to December also showing that to bigger disposition of these elements there was bigger production that practically were reached between October and December. The elements like the potassium, calcium, sulfur, copper and boron from the beginning date so far end showed a tendency to diminish arriving at its critical levels in the date between October and December also showing that among bigger decrease of the concentration of these elements in the leaves had an increase in the production The iron and magnesium increased and they diminished as it lapsed the period but always inside the value I criticize, The sector with more yield was Cinnamon tree (Chart 3) between October and November those which the values of its concentrations at level to foliate was taken to establish them as local critics (Chart 4). One can deduce that the production increases starting from the months of October and November when it begins since not the rainy period the plant you too much stress for the deficit of water to weigh that the cultivation has permanent watering what is not maybe enough or appropriate to be able to replace the necessity hídrica.